Shariah Lawyership system and its applications in Malaysia - Muhammad Husni, Ahmad (Jordan, 2013)
This study tackles an important aspect of lawyership in its application in the present era. The problem of the study lies in knowing the extent of the impact of customs and traditions in their role in society and evaluated in the light of the contemporary reality. The study also aims to shed light on the status of lawyership and its practice. The study used the historical and inductive methods to collect material, and doctrinal and analytical approach to analyse the reported opinions and applied them to reach to convincing results. The study was able to know the status of lawyership and its system in Islamic and Malaysian society and its role in the Islamic civilization. Masculinity is not a requirement in lawyership as women proved their capabilities in this field. Selection of shariah lawyers is done by a competent committee in this field.